Atrial tachycardia with cycle length alternans - Korkmaz, Ahmet; Özeke, Özcan; Çay, Serkan; Özcan, Fırat; Kara, Meryem; Özcan Çetin, Elif Hande; Beton, Nur; Aksoy, Atik; Sarıbaş, Halenur; Merovci, İdriz; Demirhan, Can; Aras, Dursun (MediaSphere Medical LLC, 2023)
Tachycardia-induced tachycardia, or so-called double tachycardia, appears to be a relatively rare condition. The underlying mechanism for stable beat-to-beat cycle length variability (alternans) in atrial tachycardia has been sparsely reported.
Keywords: Atrial Tachycardia; Double Tachycardia; Dual Loop; Multiple Loops